VALPROIC ACID INDUCES APOPTOSIS AND INCREASES CXCR7 EXPRESSION IN EPITHELIAL OVARIAN CANCER CELL LINE SKOV-3. - Salam Nasreddine; Fatima Salameh; Khodor Haidar Hassan; Ahmad Daher; Mohamad Nasser; Hassan Rammal; Akram Hijazi; Alissar Cheaib; Ola Hadadeh; Hussein Fayyad-Kazan; Mohamad Mortada; Bassam Badran (European Scientific Journal, ESJ, 2015)
Background: The chemokine receptor, CXCR7 is described to play a biologically relevant role in tumor growth and spread. Recently, it was reported that CXCR7 overexpression is associated with an unfavorable prognosis and metastatis of epithelial ovarian cancer (EOC). Aware that, several reports indicated that Histone deacetylases (HDACs) regulate the expression and activity of many proteins involved in both cancer initiation and progression, the aim of this work, was to study the effect of the HDAC inhibitor valproic acid (VPA) on the expression of CXCR7 as well as its impact on survival function in the epithelial ovarian cell line (SKOV-3). Methods: cells were cultured with varying concentrations of VPA (1, 2, 3, 4, 5 and 10 mM) for different durations (0, 12 h, 24 h and 48 h). Cell survival was assessed by Neutral red assay and by colony counting which being stained with crystal violet. CXCR7 expression was determined at mRNA level using quantitative real-time PCR (qRT-PCR) or at the protein level using western blotting. Results: VPA reduces cell survival of SKOV-3 cancer cells. The inhibition effect of VPA was dose and time-dependent. Exposure to VPA at concentrations above 2 mM at 24 h resulted in an increase expression of CXCR7 at both the mRNA and protein levels . Conclusion: These observations provide, for the first time, a better insight into the epigenetic mechanisms involved in regulating CXCR7 expression in EOC and will open new avenues for evaluating drugs that specifically stimulate the apoptosis of EOC with minimal unwanted side effects